2018
DOI: 10.2174/1389200219666180529112913
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Plays a Key Role in the Pharmacokinetic Changes of Drugs at High Altitude

Abstract: The findings of this review have indicated that hypoxia may play a key role in the PK changes of drugs at high altitude. It is suggested that patient living at or traveling to high altitude should be closely monitored, and the dosages of some drugs metabolized should be reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Of these, the Qinghai-Tibetan plateau is the largest and highest in the world, with almost 9 million inhabitants living in long-term high-altitude hypoxia. In recent years, more people have moved to the plateau regions due to social and economic development (Zhou et al, 2018). Hypoxia-induced fluctuations in organism function, metabolism, and structure underly the pathological basis of disease at high altitude (Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, the Qinghai-Tibetan plateau is the largest and highest in the world, with almost 9 million inhabitants living in long-term high-altitude hypoxia. In recent years, more people have moved to the plateau regions due to social and economic development (Zhou et al, 2018). Hypoxia-induced fluctuations in organism function, metabolism, and structure underly the pathological basis of disease at high altitude (Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more people have moved to the plateau regions due to social and economic development (Zhou et al, 2018). Hypoxia-induced fluctuations in organism function, metabolism, and structure underly the pathological basis of disease at high altitude (Zhou et al, 2018). High-altitude hypoxia has negative effects on the cardiovascular system, nervous system, and metabolism, which contribute to potential changes in drug metabolism (Mairbaurl, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one of the most disturbing findings was the deleterious effect of IH on nGSH growth promotion. While this phenomenon has not been appreciably investigated, particularly in ELGANs who experience frequent IH and apneic events during the first few weeks of life, there are a few studies that have shown that IH impairs drug metabolism [ 64 , 65 , 66 ], suggesting reduced efficacy. This may have a significant impact on pharmacokinetics in ELGANs who are exposed to numerous drugs due to multiple morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…The metabonomics of drug interventions was a concept originally put forward by Clayton in 2006, 47 and metabonomics analysis of hypoxia drugs at high altitude can be used to determine the changes in endogenous metabolites in hypoxia models after drug interventions. 48 Revealing the metabolic pathways associated with drug interventions and the pharmacological mechanisms of high-altitude hypoxia drugs will improve effective drug treatments and provide new ideas for individualized treatment.…”
Section: Metabonomics Of Drug Interventions In Plateau Hypoxiamentioning
confidence: 99%